Multiple drug allergies in a patient with acute pancreatitis: case report - Shang, Qin; Jiang, Yuanxi; Yang, Zhengyi; Yu, Diao; Qin, Li; Zhang, Xu (Frontiers in Medicine, 2025)
This study mainly reports a case of a middle-aged man who was admitted to the hospital due to sudden upper abdominal pain after several hours. After being given the painkiller compound diclofenac sodium in the outpatient clinic, the patient suffered from systemic itching, redness, and rash. Acute pancreatitis was diagnosed after admission. During the treatment, the patient had allergic reactions to multiple drugs. This case is rare. In this case, case reports are used for improving the understanding of multi-drug allergies by clinical pharmacists and clinicians, which offers certain reference for dealing with the safety and effectiveness of medication in patients undergoing multi-drug allergies.